Numerical Analysis of Polymer Foam Composite Material (PFCM) Reinforced by Palm Empty Bunch Fiber (PEBF) at Fracture Point Due to High Strain Impact Load - Achmad Jusuf Zulfikar; Siswo Pranoto; Bobby Umroh; Darianto Darianto; Gustami Harahap (Budapest International Research and Critics University, 2020)
In general, polymer composite materials are molded in solid form and avoid the occurrence of gas bubbles trapped in the matrix. The resulting material becomes rigid and does not have a good ability to absorb the load given. At this time, innovations in the field of composite materials have been carried out and produced polymer composite materials with foam-shaped structures that are able to reduce the load given. In this study, a composite foam material reinforced with PEBF fiber was tested with an impact dynamic load and the test results were numerically analyzed by the finite element method. The purpose of this study is to obtain the stress distribution at the fracture point due to the impact of dynamic loads at high strain rates with the finite element analysis method. Impact dynamic test using the Air Gun Compressor (AGC) test with an impact pressure of 0.2 – 0.8 MPa. Strain wave propagation in the test specimen was recorded using two strain gauges. Numerical analysis is carried out with the help of Msc. Nastran software. Experimentally, a failure in the specimen occurred at an impact pressure of 0.4 MPa and an impact distance (ID) of 500 mm. Strain wave propagation time in the specimen averaged 37.5 ms, at which time the tensile and compressive stresses intersected at a distance of about 120 to 155 mm from the starting point of loading. The magnitude of the stress distribution in the range of the fracture zone is between 800 to 900 MPa.